Grub chen Ñi zla kun mdzes kyi gsuṅ ʼbum las Ñams mgur skor skal bzaṅ thar lam ʼgod paʼi phrin las : the experiential songs (ñams mgur) of Ñag-bla Padma-bdud-ʼdul (Ñi-zla-kun-mdzes) - Padma-bdud-ʼdul, Ñag-bla, 1816-1872 (N. Sonam ; distributor, Tibetan Bonpo Monastic Centre, 1975)
Songs of esoteric realization of a religious teacher of the Nyingmapa tradition from the Nyarong area in the Sino-Tibetan borderland.